MOBILE ASSISTED LANGUAGE LEARNING: EFL LEARNERS’ PERCEPTIONS TOWARD THE USE OF MOBILE APPLICATIONS IN LEARNING ENGLISH - Endang Darsih; Nida Amalia Asikin (English Review: Journal of English Education, 2020)
Although extensive research has been carried out on the positive effect of Mobile Assisted Language Learning (MALL) for students’ learning, there have been few studies concerning on university students’ perceptions toward the use of MALL in learning English. The study was undertaken to examine university students’ perceptions toward MALL specifically the use of mobile application in learning English. The participants of this study were ninety six students (68 females and 28 males). Data collection instruments used in this study were questionnaire and semi-structured interview. It reported that all participants apply MALL by downloading and using English mobile applications to help their learning. Six mobile applications which are often used by all participants were Kamusku, Google Translate, Elsa Speak, Youtube, Zoom and Google Meet. The results of the questionnaires also showed that their perceptions toward the use of MALL was that MALL, in this case the English mobile application was considered to be useful and helped their learning, besides it was overall easy to use.